Fenomena Rujuk Setelah Talak Tiga: Kajian Hukum Keluarga Islam - Indah Hoirunnisah; Zuraidah (CV. Doki Course and Training, 2025)
This study aims to examine the phenomenon in the Ilir Barat II Palembang District Community who reconciled with their partners after triple divorce from the perspective of Islamic law. The reconciliation was carried out without heeding the rules contained in Islamic family law which requires the ex-wife to marry another man first without any engineering and to divorce purely, only then can the first ex-husband remarry his ex-wife. This study is an empirical legal study, using qualitative data and the data sources used are primary data and secondary data. The data obtained will be analyzed descriptively qualitatively, then will be concluded deductively. The results of the study found that the cause of the deviation in the relationship after triple divorce in the Ilir Barat II Palembang District was due to a lack of understanding of religious knowledge and a desire to immediately reconcile without following a complicated process. Based on the study of Islamic law, reconciliation is forbidden, even if they have sexual relations, it is said to be adultery. This is because they do not make a new contract, they also do not follow the provisions of the sharia which require the ex-wife to marry another man and divorce her new husband, only then can the first ex-husband remarry his ex-wife.